Nilpotent control systems - Remm, Elisabeth; Goze, Michel (Revista Matemática Complutense, 2002)
We study the class of matrix controlled systems associated to graded filiform nilpotent Lie algebras. This generalizes the nonlinear system corresponding to the control of the trails pulled by car.